Preventing stunting among adolescents by increasing knowledge and awareness of local food utilization - Nur Aini Mahmudah; Nur Agustin Mardiana; Aditya Wirawantoro Putra; Panji Purnomo; Anang Widigdyo; David Kurniawan (Universitas Muhammadiyah Malang, 2024)
Stunting remains a critical public health issue in Indonesia. The